2008
DOI: 10.1038/ismej.2008.12
|View full text |Cite
|
Sign up to set email alerts
|

Micro-scale observations of the structure of aerobic microbial granules used for the treatment of nutrient-rich industrial wastewater

Abstract: The structure and function of aerobic microbial granules from a lab-scale sequencing batch reactor treating nutrient-rich abattoir wastewater were investigated. These wastewater-fed granules were examined using a wide range of micro-scale techniques including light microscopy, scanning and transmission electron microscopy, fluorescent in situ hybridisation (FISH) combined with confocal laser scanning microscopy and oxygen and pH microsensors, in conjunction with a range of measurements in the bulk liquid phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
105
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 40 publications
10
105
2
2
Order By: Relevance
“…Subsequent decay could give rise to formation of voids occupying 13 to 17% of the anoxic zone. In contrast to voids observed in aerobic granules (18), no connections were seen between a void and the outside of a granule.…”
Section: Anaob Vssmentioning
confidence: 51%
See 1 more Smart Citation
“…Subsequent decay could give rise to formation of voids occupying 13 to 17% of the anoxic zone. In contrast to voids observed in aerobic granules (18), no connections were seen between a void and the outside of a granule.…”
Section: Anaob Vssmentioning
confidence: 51%
“…In suspended biomass systems, settling properties determine the retention of biomass and are related to the microbial aggregate morphology (floc or granule) and size. Granules can be defined as compact and dense aggregates with an approximately spherical external appearance that do not coagulate under decreased hydrodynamic shear conditions and settle significantly faster than flocs (18). Toh and coworkers calculated a lower sludge volume index for aerobic granules than for aerobic flocs and also showed that there was an increase in the settling velocity with increasing granule size (35).…”
mentioning
confidence: 99%
“…treating the complex abattoir wastewater appeared highly dominated by Accumulibacter-like bacteria (approximately 80 to 90%), as revealed by FISH images of entire granule sections (31). In relative terms, it is possible that the intuitively expected high richness values due to more complex wastewaters may be counteracted by the strong physical and redox change selection pressure applied in the anaerobic-aerobic sequencing batch reactors.…”
mentioning
confidence: 98%
“…Although this approach has increased our understanding of the process, models are often only validated against macroscale results with limited or no microscale observations (21,22). Despite the fact that the physical architecture of the granules is intrinsically related to mass transport, conversion processes and niches partitioning within the granules, few reports describe details on the microstructure of aerobic granules (23,24). In addition, an effective approach to stain all of the constituents of the aggregates is required because most previous research has focused on fluorescence methods to target specific bacterial types.…”
mentioning
confidence: 99%